ANALISIS VISUAL SAMPUL MAJALAH “BOBO” EDISI BULAN APRIL 2016 - Ni Nyoman Sri Witari; Ketut Nala Hari Wardana (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
Bobo Magazine is one of children’s magazine which is still exsisted from 1974 until now. Their cover has its own uniqueness. This research was aimed at identifying visual layout of Bobo Magazine, finding the quality of element’s design and visuals elements. The research method is qualitative approach which are collected from observation results, documentation and library research. The object of research was Bobo’s magazine cover of April edition, 2016. The data analysis used to analyze visualization quality was the theory of Tom Lincy about five principal design on printed works, such as proportion, balance, contrast, rhyme, and unity. From the visual data analysis it was found that layout composition from illustration, texts/letter, and colour on cover has applied the principles of unity, balance, rhyme, contrast and proportion. The visual’s fascination is unique, different from others, because it was supported by the use of Bobo’s family characters as icons, the use of bright pastel colours, the use of exact San Serif letters and dynamic layout of objects